Optical design of perovskite solar cells for applications in monolithic tandem configuration with CuInSe2 bottom cells. (25th May 2018) - Ahangharnejhad, Ramez H.; Song, Zhaoning; Phillips, Adam B.; Watthage, Suneth C.; Almutawah, Zahrah S.; Sapkota, Dhurba R; Koirala, Prakash; Collins, Robert W.; Yan, Yanfa; Heben, Michael J.
Abstract: Monolithic integrated thin film tandem solar cells consisting of a high bandgap perovskite top cell and a low bandgap thin film bottom cell are expected to reach higher power conversion efficiencies (PCEs) with lower manufacturing cost and environmental impacts than the market-dominant crystalline silicon photovoltaics. There have been several demonstrations of 4-terminal and 2-terminal perovskite tandem devices with CuInGaSe2 (CIGS) or CuInSe2 (CIS) and, similar to the other tandem structures, the optimization of this device relies on optimal choice for the perovskite bandgap and thickness. Therefore, further advancement will be enabled by tuning the perovskite absorber to maximize the photocurrent limited by the current match condition. Here, we systematically study the optical absorption and transmission of perovskite thin films with varying absorber band gap. Based on these results, we model the photocurrent generations in both perovskite and CIS subcells and estimate the performances of projected tandem devices by considering the ideally functioning perovskite and CIS device. Our results show that for perovskite layers with 500 nm thickness the optimal bandgap is around 1.6 eV. With these configurations, PCEs above 20% could be achieved by monolithically integrated perovskite/CIS tandem solar cells. Also by modelling the absorption at every layer we calculate the quantum efficiency at each subcell in addition to tracking optical losses.